1997
DOI: 10.3109/00016349709047818
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of an absent end‐diastolic velocity in the umbilical artery detected before the 34th week of pregnancy

Abstract: An early ARED finding (before the 34th week) in the umbilical artery signifies a marked warning signal of fetal distress. In these cases the rates of perinatal morbidity and mortality are very high, which is a reflection of the severity of the condition. The majority of fetuses can, however, be saved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
13

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
(10 reference statements)
0
16
0
13
Order By: Relevance
“…[ [11][12][13][14][15][16] In a large study on 145 growth restricted fetuses from Italy, Cosmi and co-workers [17] reported that neonatal death was increased in fetuses with umbilical artery reversed flow (P<.05). They also concluded that fetuses with idiopathic growth restriction, low birth weight, umbilical artery reversed flow and ductus venosus absent or reversed flow, had an increased perinatal morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…[ [11][12][13][14][15][16] In a large study on 145 growth restricted fetuses from Italy, Cosmi and co-workers [17] reported that neonatal death was increased in fetuses with umbilical artery reversed flow (P<.05). They also concluded that fetuses with idiopathic growth restriction, low birth weight, umbilical artery reversed flow and ductus venosus absent or reversed flow, had an increased perinatal morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…A mortalidade perinatal é elevada, variando de 15 a 62% nas maiores casuísticas referidas na literatura 16,17 . Na Clínica Obstétrica do HC-FMUSP, no período compreendido entre 1992 e 1999, a mortalidade perinatal observada entre estes casos foi de 35,8% 18 .…”
Section: Discussionunclassified
“…Simultaneamente, no territó-rio venoso descreve-se ainda fluxo preferencial pelo ducto venoso também com o objetivo de favorecer a oxigenação daquelas áreas 31 .…”
Section: Resposta Fetal à Hipoxia E Avaliação Da Vitalidade Fetalunclassified